2022
DOI: 10.1017/s0031182022001317
|View full text |Cite
|
Sign up to set email alerts
|

Beta diversity, prevalence, and specificity of avian haemosporidian parasites throughout the annual cycle of Chilean Elaenia (Elaenia chilensis), a Neotropical austral migrant

Abstract: Migratory birds are implicated in dispersing haemosporidian parasites over great geographic distances. However, their role in sharing these vector-transmitted blood parasites with resident avian host species along their migration flyway is not well understood. We studied avian haemosporidian parasites in 10 localities where Chilean Elaenia, a long-distance Neotropical austral migrant species, spends part of its annual cycle to determine local parasite transmission among resident sympatric host species in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…Here, we observed that avian haemosporidians are specialized, infecting more commonly a speci c set of hosts. We also revealed specialization changes between distinct parasites, with Plasmodium lineages infecting a wider range of hosts than Haemoproteus (Fecchio et al 2022). When evaluating the ve more abundant species sampled in this study, we observed that all species present higher specialization and are infected by less distinct parasite lineages than expected, reinforcing the high degree of specialization observed when evaluating parasites.…”
Section: Discussionsupporting
confidence: 71%
“…Here, we observed that avian haemosporidians are specialized, infecting more commonly a speci c set of hosts. We also revealed specialization changes between distinct parasites, with Plasmodium lineages infecting a wider range of hosts than Haemoproteus (Fecchio et al 2022). When evaluating the ve more abundant species sampled in this study, we observed that all species present higher specialization and are infected by less distinct parasite lineages than expected, reinforcing the high degree of specialization observed when evaluating parasites.…”
Section: Discussionsupporting
confidence: 71%
“…This may explain the discrepancy between past research findings and the conclusions of the present study. Indeed, past research on large‐scale parasite turnover has confirmed this pattern among haemosporidians and other parasite taxa (Dallas and Poisot 2018, Fecchio et al 2019b, 2022, Martins et al 2021). Therefore, geographic distance might only play an important role in shaping parasite turnover at larger scales or when there is a higher degree of heterogeneity among sites, whereas landscape and host features are the most important factors determining parasite turnover at smaller scales or among more homogeneous environmental conditions.…”
Section: Discussionmentioning
confidence: 79%
“…Previous research has evaluated factors driving haemosporidian turnover at local and regional scales (Williamson et al 2019, McNew et al 2021, de La Torre et al 2022, Fecchio et al 2022). Some found that geographic distance was not the principal driver of parasite turnover.…”
Section: Discussionmentioning
confidence: 99%